Adipose-Tissue and Intestinal Inflammation – Visceral Obesity and Creeping Fat - Kredel, Lea I.; Siegmund, Britta (Frontiers in Immunology, 2014)
Obesity has become one of the main threats to health worldwide and therefore gained increasing clinical and economic significance as well as scientific attention. General adipose tissue accumulation in obesity is associated with systemically increased pro-inflammatory mediators and humoral and cellular changes within this compartment. These adipose tissue changes and their systemic consequences led to the concept of obesity as a chronic inflammatory state. A pathognomonic feature of Crohn’s disease (CD) is creeping fat (CF), a locally restricted hyperplasia of the mesenteric fat adjacent to the inflamed segments of the intestine. The precise role of this adipose tissue and its mediators remains controversial, and ongoing work will have to define whether this compartment is protecting from or contributing to disease activity. This review aims to outline specific cellular changes within the adipose tissue, occurring in either obesity or creeping fat. Hence the potential impact of adipocytes and resident immune cells from the innate and adaptive immune system will be discussed for both diseases. The second part focuses on the impact of generalized adipose-tissue accumulation in obesity, respectively on the locally restricted form in CD, on intestinal inflammation and on the closely related integrity of the mucosal barrier.